Faktor-Faktor Faktor-Faktor Yang Mempengaruhi Produktivitas Penyadap Tanaman Karet di PT. Atjeh Raya Corpindo Kebun Alur Buluh - Muhammad Hamdani Muhammad Hamdani; Rozalina; Kiagus Muhammad Zain Basriwijaya (JURNAL AGRICA, 2023)
Aceh Province has the potential for extensive rubber plant development, where in 2020 the area of rubber plants in Aceh reached 121,551 Ha with a production of 63,854 tons. Rubber plantations in Aceh Province are spread in most districts in Aceh Province, one of which is East Aceh District where the rubber land area in East Aceh reaches 22,520 Ha. High and low productivity is caused by several factors, one of which is the employee tapping the rubber plant itself. This study aims to determine what factors affect the productivity of the performance of rubber plant tapper employees at PT Atjeh Raya Corpindo Kebun Alur Buluh, Birem Bayeun District, East Aceh Regency. The sampling technique uses the Simple Random Sampling technique. To find out what factors affect the productivity of the performance of employees tapping rubber plants used statistical analysis with multiple linear methods. The results of this study indicate that the variables of work environment, supervision, and premium partially have a significant effect on the productivity of the performance of rubber plant tappers. The experience variable partially has no significant effect on the productivity of the performance of rubber plant tappers.